2013
DOI: 10.1016/j.tcs.2013.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Solving the at-most-once problem with nearly optimal effectiveness

Abstract: We present and analyze a wait-free deterministic algorithm for solving the at-most-once problem: how m shared-memory fail-prone processes perform asynchronously n jobs at most once. Our algorithmic strategy provides for the first time nearly optimal effectiveness, which is a measure that expresses the total number of jobs completed in the worst case. The effectiveness of our algorithm equals n − 2m + 2. This is up to an additive factor of m close to the known effectiveness upper bound n − m + 1 over all possib… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…They gave a lower bound on the number of performed tasks, showing that it was impossible to perform all tasks, and gave an algorithm with effectiveness close to the lower bound. Kentros and Kiayias [41] solve At-Most-Once with improved effectiveness. Kentros et al [40] introduced the Strong-At-Most-Once problem, in which all tasks must be performed in the absence of crashes, and showed that it has consensus number 2.…”
Section: Introductionmentioning
confidence: 99%
“…They gave a lower bound on the number of performed tasks, showing that it was impossible to perform all tasks, and gave an algorithm with effectiveness close to the lower bound. Kentros and Kiayias [41] solve At-Most-Once with improved effectiveness. Kentros et al [40] introduced the Strong-At-Most-Once problem, in which all tasks must be performed in the absence of crashes, and showed that it has consensus number 2.…”
Section: Introductionmentioning
confidence: 99%